Peran Guru dalam Membangun Keterampilan Komunikasi Anak Usia Dini - Dewinta sari; Diva Amalia; Fany Padilah; Hamidah Hanum Siregar; Elya Siska Anggraini (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Communication is a fundamental skill that must be developed from an early age. These skills influence children's ability to interact socially and academically in the future. Teachers, as the main facilitators in the early childhood education environment, have a crucial role in developing these skills. This article aims to identify how the teacher's role influences communication skills in early childhood. This research uses a qualitative approach with surveys as the main method. This qualitative research involves data through in-depth interviews, observation and document analysis. The results of data analysis show that teachers who create a language-rich classroom environment use interactive learning methods, such as storytelling, role playing, providing picture books and other printed materials which are effective in improving children's communication skills. Children who are in a supportive environment are more likely to actively talk and listen. Teachers who model good communication by using clear and precise language help children improve their speaking skills